Dactylogyrus Scrjabinensis (Monogenea: Dactylogyride): First Occurrence on The Gills of Capoeta Trutta From Iraq - Abdullah, Younis S.; Abdullah, Shamall Mohammad Amin A. (Science Journal of University of Zakho, 2014)
The momogenean Dactylogyrus scrjabinensis Osmanov, 1958 was identified on the gills of the cyprinid fish Capoeta trutta (Heckel, 1843) from Sirwan river, southeast of Sulaimani governorate, Kurdistan region, during the period from April to August 2014, in the present study for the first time in Iraq. The full details of description and measurements of this parasite are given. The prevalence and intensity of infection were 3.94% and 3.66 respectively.
Keywords: Dactylogyrus scrjabinensis; Capoeta trutta; Sirwan river; Iraq